To Evaluate Different Doses of Intravenous Lignocaine on the Incidence of Etomidate Induced Myoclonus - Singhal, Saurabh; Gupta, Rahul (Academia Anesthesiologica International, 2019)
Background: Induction of anesthesia with etomidate results in dose-dependent myoclonus. The present study was conducted to evaluate different doses of intravenous lignocaine on the incidence of Etomidate induced myoclonus. Subjects and Methods: The present study was conducted in the department of Anesthesia. It comprised of 90 patients. Patients were divided into 3 groups of 30 each. In group I patients, 6 mL of normal saline was given and in group II patients, 0.5 mg/kg of lignocaine was given and in group III patients, 1 mg/kg lignocaine diluted to 6 mL (with NS) was given. The four?point intensity scoring was used. Results: Out of 90 patients, males were 45 and females were 45. Mean weight of patients in group I was 56.4 years, in group II was 60.4 years and group III was 58.9 years. ASA grade was I in 19 in group I, 20 in group II and 22 in group III. It was grade II seen in 11 in group I, 10 in group II and 8 in group III. Grade 0 was seen in 30% in group I, 55% in grade II and 60% in grade III, grade 1 was seen 20% in group I, 15% in group II and 20% in group III, grade 2 in 15% in group I, 20% in group II and 10% in group III, grade 3 was seen in 35% in group I, 10% in group II and 10% in group III. The difference was significant (P< 0.05). Conclusion: Different doses of lignocaine resulted in variation in Myoclonus. It was observed that 1 mg/kg of lignocaine was effective than other doses in reducing the incidence of EM.